2018
DOI: 10.1016/j.bjid.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Is Visceral Leishmaniasis the same in HIV-coinfected adults?

Abstract: Clinical and laboratory presentation of Visceral Leishmaniasis in HIV-coinfected patients may differ from classic kala-azar, and these differences may be, in part, responsible for the delay in diagnosing and treating leishmaniasis, which might lead to worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
1
14
0
1
Order By: Relevance
“…The clinical presentation of VL in the presence of HIV infection may be atypical; for example, the classical triad (fever, constitutional symptoms and splenomegaly), as well as jaundice and edema, is less frequently observed 25 . Accordingly, the diagnosis of VL is more difficult in individuals with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of VL in the presence of HIV infection may be atypical; for example, the classical triad (fever, constitutional symptoms and splenomegaly), as well as jaundice and edema, is less frequently observed 25 . Accordingly, the diagnosis of VL is more difficult in individuals with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, fever was 250 observed more frequently in patients with VL than those with VL/HIV co-infection, [23,28]. Different 254 from many Brazilian studies, which reported the presence of splenomegaly followed by 255 fever, weight loss, and asthenia, in 81 patients with VL/HIV co-infection in Ceará [29] 256 and another study that identified weight loss, weakness, fever, and hepatosplenomegaly 257 as the most common physical changes in 65 patients with VL/HIV co-infection [13], the 258 most common symptoms in this study were skin pallor, hepatomegaly, and levels observed in some patients with VL/HIV co-infection [33,34,35] was also found in 279 the present study. However, we should note that such an increase was higher in patients 280 with VL alone, as additionally reported by De Souza et al and Cota et al [25,36].…”
mentioning
confidence: 83%
“…HIV infection is also strongly associated with a higher prevalence of chronic human papillomavirus, resulting in increased risk for anal cancer [40]. In HIV-Leishmania coinfected patients, visceral leishmaniosis can accelerate disease, decreasing the likelihood of patient survival [41]. C. neoformans and H. capsulatum are the only agents that have been isolated, particularly from immunocompromised individuals [14,16].…”
Section: Opportunistic Infections and Coinfectionmentioning
confidence: 99%